2022
DOI: 10.3390/ijms23084235
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Proteins Unveil the Mechanism by Which Physical Exercise Ameliorates Memory, Learning and Motor Activity in Hypoxic Ischemic Encephalopathy Rat Model

Abstract: Background: Physical exercise has been shown to improve cognitive and motor functions, promoting neurogenesis and demonstrating therapeutic benefits in neurodegenerative disorders. Nonetheless, it is crucial to investigate the cellular and molecular mechanisms by which this occurs. The study aimed to investigate and evaluate the effect of swimming exercise on the changes of mitochondrial proteins in the brains of rats with hypoxic ischemic encephalopathy (HIE). Methods: the vertical pole and Morris water maze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The GO analysis indicated that the downregulated DEGs were mainly associated with biological processes related to nervous system development, neuron generation, and neurogenesis. Increasing evidence has demonstrated that the disruption of neurogenesis in the hippocampus significantly contributes to the development of cognitive impairment following neonatal HIBD 35,36 . The activation of the BDNF/TrkB signaling pathway plays a crucial role in reducing cell death in the vicinity of lesions, repairing neuronal damage, and facilitating neurogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO analysis indicated that the downregulated DEGs were mainly associated with biological processes related to nervous system development, neuron generation, and neurogenesis. Increasing evidence has demonstrated that the disruption of neurogenesis in the hippocampus significantly contributes to the development of cognitive impairment following neonatal HIBD 35,36 . The activation of the BDNF/TrkB signaling pathway plays a crucial role in reducing cell death in the vicinity of lesions, repairing neuronal damage, and facilitating neurogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that the disruption of neurogenesis in the hippocampus significantly contributes to the development of cognitive impairment following neonatal HIBD. 35 , 36 The activation of the BDNF/TrkB signaling pathway plays a crucial role in reducing cell death in the vicinity of lesions, repairing neuronal damage, and facilitating neurogenesis. 37 To identify a potential therapeutic target for treating neonatal HIBD, we investigated the neuroprotective effects of DEX on neurogenesis in the hippocampus through the BDNF/TrkB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1 can compensate for PINK1 function, while DJ-1 mutations inhibit mitophagy, leading to the accumulation of obsolete mitochondria and inducing neurodegenerative lesions that, in turn, induce PD. The DJ-1 gene was up-regulated in the frontal cortex of rats after exercise, maintaining mitochondrial proteostasis and thereby delaying PD symptoms [117,118].…”
Section: Exercise Improves Pd By Modulating Mitophagymentioning
confidence: 99%
“…In the hypoxic ischemic encephalopathy rat model, endurance training preserved hippocampal and cerebral cortical mitochondrial membrane integrity to lower cytoplasmic and nuclear levels of the mitochondrial apoptosis-inducing proteins AIF and cytochrome c, as well as cleaved caspase-3. The antiapoptotic impact of exercise training improved motor function, learning, and memory suggesting that exercise training stabilizes mitochondrial function to protect against cell death in neurodegenerative disease [ 142 ].…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 99%